Formation and C–F bond functionalization of [P, N]-ligated perfluoronickelacyclopentanes. (1st January 2019) - Giffin, Kaitie A.; Pua, Lorraine A.; Korobkov, Ilia; Baker, R. Tom
Graphical abstract: Synthesis and characterization of[P, N] -ligated perfluoronickelacyclopentanes based on the bidentate ligand 2-(diphenylphosphino)phenyl- N -phenylaniline[P, NH] are reported. Reactivity studies of the phosphinoamine[P, NH] - and anionic phosphinoamide[P, N − ] -ligated perfluoronickelacycles are presented. Abstract: Detailed herein is the synthesis and characterization of[P, N] -ligated perfluoronickelacyclopentanes based on the bidentate ligand 2-(diphenylphosphino)phenyl- N -phenylaniline[P, NH] . A high-yielding substitution reaction between [P(O- o -tol)3 ]2 Ni(C4 F8 ) and[P, NH] gives the phosphine-amine-coordinated metallacycle [P, NH]Ni(C4 F8 ). Alternatively, [P, NH]Ni(C4 F8 ) is formed upon treatment of Ni[P(O- o -tol)3 ]4 with one equiv. of[P, NH] followed by tetrafluoroethylene. This product reacts quantitatively with base to give an anionic phosphine-amido-ligated nickelacycle. Reactivity studies of the new[P, NH] - and[P, N − ] -ligated perfluoronickelacycles are presented and compared and contrasted with our previously reported[P, S] systems.